PENGARUH ROTASI KAP, AUDITTENURE,DAN REPUTASI KAP TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR - Siska Nurhayati; Sawitri Dwi Prastiti (Universitas Negeri Malang, 2015)
This research aims to explaine mandatory rotation of audit firm, audit tenure, and accounting firm reputation toward audit quality, measured by discretionary accruals. Samples are manufacturing firms listed in Indonesia Stock Exchange for the year 2008 until 2012 with total observations of 819 firm-years. Multiple regression is used for hypotheses testing. The results show that there is no significant effect of mandatory rotation of audit firm on audit quality. Audit firms and auditee can be considered well known of PMK 17/PMK.01/2008. Then audit tenure and audit firms reputation have significant effect to audit quality. Audit tenure can be consedered increase competencies of auditor, while the audit firms reputation that affiliated with big 4 firms probably has well integrity.Keywords: mandatory rotation of audit firm, audit tenure, audit firms reputation, audit quality